2011
DOI: 10.4314/pamj.v8i1.71154
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastoma of scaphoid of the carpus: a case report

Abstract: Osteoblastoma is a rather uncommon tumor, especially when located in the wrist (and hand). Its diagnosis therefore appears to be problematic. We describe a case of osteoblastoma of the scaphoid bone and its management. To our knowledge, this is the fourth case of osteoblatoma of the carpus reported in the literature. Proximal row carpectomy was chosen because of the aggressive nature of the tumor. A tendon transfer was performed in the same session for wrist stabilization. Other authors have opted for a more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A literature review of reported cases of osteoblastoma arising in bones of hands and feet 7–27 is summarized in Table 1. A total of 21 relevant English articles were collected.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of reported cases of osteoblastoma arising in bones of hands and feet 7–27 is summarized in Table 1. A total of 21 relevant English articles were collected.…”
Section: Discussionmentioning
confidence: 99%